Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/biomedicines4030016
|View full text |Cite
|
Sign up to set email alerts
|

Fifty Years of Clinical Application of Newcastle Disease Virus: Time to Celebrate!

Abstract: This review provides an overview of 50 years of basic and clinical research on an oncolytic avian virus, Newcastle Disease Virus (NDV), which has particular anti-neoplastic and immune stimulatory properties. Of special interest is the fact that this biological agent induces immunogenic cell death and systemic anti-tumor immunity. Furthermore, localized oncolytic virotherapy with NDV was shown to overcome systemic tumor resistance to immune checkpoint blockade immunotherapy. Clinical experience attests to low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 73 publications
(74 reference statements)
1
75
0
3
Order By: Relevance
“…An approach for this concern is the use of oncolytic viruses, especially NDV, which had demonstrated the capability to kill malignant cells as a result of activation of apoptotic pathways, both in vitro and in vivo (2,27). However, it has been reported that treatment response is dependent on the used NDV strain (2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An approach for this concern is the use of oncolytic viruses, especially NDV, which had demonstrated the capability to kill malignant cells as a result of activation of apoptotic pathways, both in vitro and in vivo (2,27). However, it has been reported that treatment response is dependent on the used NDV strain (2).…”
Section: Discussionmentioning
confidence: 99%
“…An approach for this concern is the use of oncolytic viruses, especially NDV, which had demonstrated the capability to kill malignant cells as a result of activation of apoptotic pathways, both in vitro and in vivo (2,27). However, it has been reported that treatment response is dependent on the used NDV strain (2). In this sense, our goal was to determine whether a recombinant attenuated NDV from a genotype V velogenic strain (22,24) possesses hemagglutinating, antitumor and immunostimulatory activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations